2018
DOI: 10.14310/horm.2002.1757
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, pathogenesis and management of prediabetes and type 2 diabetes mellitus in patients with polycystic ovary syndrome

Abstract: Polycystic ovary syndrome (PCos) is the most common endocrinopathy in women of reproductive age. PCos is not only the leading cause of anovulatory infertility but is also associated with an array of metabolic disorders, among which impaired glucose metabolism has been a topic of intense research. The aim of the present narrative review is to summarize the findings of the studies that have evaluated the prevalence and incidence of prediabetes and type 2 diabetes mellitus (T2Dm) in patients with PCos, to analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 81 publications
1
6
0
Order By: Relevance
“…It was evident that the diameter of large follicles before ovulation in Xinji fine-wool sheep is significantly larger than that in Small Tail Han sheep. That Small Tail Han sheep were found to have more large follicles (distributed on both ovaries) in the present study was consistent with the findings of Lazaridou et al (2017 ). This study found that in the natural estrus cycle of sheep, the FSH, E2, and P4 levels in Small Tail Han sheep were significantly higher than those in Xinji fine-wool sheep.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It was evident that the diameter of large follicles before ovulation in Xinji fine-wool sheep is significantly larger than that in Small Tail Han sheep. That Small Tail Han sheep were found to have more large follicles (distributed on both ovaries) in the present study was consistent with the findings of Lazaridou et al (2017 ). This study found that in the natural estrus cycle of sheep, the FSH, E2, and P4 levels in Small Tail Han sheep were significantly higher than those in Xinji fine-wool sheep.…”
Section: Discussionsupporting
confidence: 92%
“…According to the present study, it was speculated that the lower expression of HSD17B1 in Small Tail Han sheep decreases E2, P4, and ACT secretion and further reduce the apoptosis of granulosa cells, which could have maintained the development of follicles. The function of regulating these sex steroids of HSD17B1 in granulosa cells had previously been reported in rats, mice, and horses ( McGee and Hsueh, 2000 ; Gangloff et al, 2001 ; Zhang et al, 2012 ; Lazaridou et al, 2017 ). This study confirmed that HSD17B1 might play a similar role in sheep.…”
Section: Discussionmentioning
confidence: 81%
“…Women with PCOS often suffer from comorbidities related to metabolic, psychological, and reproductive factors. Compared with women without PCOS, they have higher prevalence of insulin resistance, type 2 diabetes, metabolic syndrome, non‐alcoholic fatty liver disease, obesity, hypertension, and risk for cardiovascular diseases 3–5 . Obesity exacerbates most co‐morbidities and symptoms associated with PCOS 6 .…”
Section: Introductionmentioning
confidence: 99%
“…The various hormonal disturbances in PCOS predispose these individuals to multiple comorbidities, such as cardiovascular disease (CVD), diabetes, and metabolic syndrome. The metabolic disorder has been well-established, with evidence of insulin resistance and hyperinsulinemia in 60-80% of all PCOS patients (Lazaridou et al, 2017). Research in PCOS has focused on managing symptoms, rather than uncovering the underlying pathogenesis to discover more clear diagnostics and targeted treatments.…”
Section: Introductionmentioning
confidence: 99%